Locally advanced prostate cancer—biochemical results from a prospective phase II study of intermittent androgen suppression for men with evidence of prostate‐specific antigen recurrence after radiotherapy - Nicholas Bruchovsky; Laurence Klotz; Juanita Crook; S. Larry Goldenberg (2007)
Abstract BACKGROUND. Biochemical results from a prospective Phase II trial of intermittent androgen suppression for recurrent prostate cancer after radiotherapy were analyzed for correlations to the onset of hormone‐refractory disease. METHODS. Patients with histologically confirmed adenocarcinoma of the prostate and a rising serum prostate‐specific antigen (PSA) level after external beam irradiation of the prostate were treated intermittently with a 36‐week course of cyproterone acetate and leuprolide acetate. Then, patients were stratified according to their serum PSA range at the start of each cycle and were followed with further biochemical testing until disease progression was evident. RESULTS. The mean PSA reduction was 95.2% irrespective of stratification group. A baseline serum PSA level <10 μg/L and a serum PSA nadir ≤0.2 μg/L were associated with the longest time off treatment. The overall mean nadir PSA value in the progression group at 1.40 ± 0.19 μg/L was 2.6‐fold greater than the value of 0.55 ± 0.88 μg/L in the no‐progression group ( P = .0002). Recovery of serum testosterone to a level of ≥7.5 nmol/L was observed in 75%, 50%, 40%, and 30% of men in Cycles 1 to 4, respectively, and was sufficient to normalize the level of hemoglobin in each cycle, which dropped by an average of 10.8 g/L during treatment ( P < .0001). CONCLUSIONS. The length of the off‐treatment interval during cyclic androgen withdrawal therapy was related inversely to baseline and nadir levels of serum PSA. Nadir PSA was a powerful predictor of early progression to androgen independence. Cancer 2007 © 2007 American Cancer Society.